Organizing control : August Thyssen and the construction of German corporate management - Fear, Jeffrey R. (Harvard studies in business history, 2005)
"In a pioneering work, Jeffrey Fear overturns the dominant understanding of German management as "backward" relative to the United States and uncovers an autonomous and sophisticated German managerial tradition. Beginning with founder August Thyssen - the Andrew Carnegie of Germany - Fear traces the evolution of management inside the Thyssen-Konzern and the Vereinigte Stahlwerke (United Steel Works) between 1871 and 1934."